Development of Solar Panel Cleaning Robot for Residential Sector - Zainuddin, Nazihah; Abdullah, Mohd Noor (Evolution in Electrical and Electronic Engineering, 2023)
The function of a solar panel is to absorb solar energy and convert it into electricity. Hence, it is required to install the solar panel in the open area to absorb the maximum radiation of sunlight. Installing the solar panel in an open area, the solar panel easily to be soiling due to dust, bird pooping, and pollen. Thus, the solar panel cannot absorb the maximum radiation of sunlight. Hence, the solar panel needs to be clean in order to generate maximum electricity. Mostly, people used manual cleaning to clean solar panels but manual cleaning is known as an old method and not an effective way because it takes a long duration in cleaning the solar panel and this method is costly due to the use of a lot of water consumption. Thus, the main objective of this project is to design and develop a solar panel cleaning robot. This project has proposed to use of a dry cleaning method by using two types of brushes which are nylon brushes and microfiber brushes. Besides that, Arduino IDE software is used to receive and process the control signal from the sensor and send the processed signal to the microcontroller which is Arduino to control the movement of the solar panel cleaning robot and the movement of the nylon brush. The robot is able to move around the solar panel according to the proposed movement where the robot will turn right when the distance of the solar panel with the robot is 2.5 cm and above while if the distance is below 2.5 cm, the robot moves forward. Besides that, from the result, it found that the robot was able to clean the solar panel under two conditions which are when the solar panel is dusted and the surface of the solar panel has leaves.